Factors Affecting Generalization of Ocular Myasthenia Gravis in Palembang - Zahratul Riadho Farid; Devi Azri Wahyuni (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2020)
Introduction: Ocular myasthenia gravis (OMG) is an autoimmune disease which is characterized by weakness of extraocular muscles, levator palpebrae and orbicularis oculi, resulting in ptosis and binocular diplopia. Nearly all patients present with eyelid and extra ocular muscles involvement. Approximately 30% to 80% of patients with OMG experience a conversion to generalized myasthenia gravis (GMG) within 2 years. There are not only have ptosis and diplopia but also limb weakness,bulbar symptoms, or even respiratory failure. Objective: To observe the clinical features of OMG to GMG and risk factors and median time to conversion of OMG to GMG of myasthenia gravis patients in Dr. Mohammad Hoesin General Hospital Palembang. Methods: This study is a cohort retrospective study and the data were collected from the medical records of 91 patients who were registered as myasthenia gravis patients during September 2018 to March 2020. Sosiodemographic and clinical characteristics, including onset of OMG to GMG, history of smoking, presence of thymic abnormalities, and medications received were reviewed retrospectively. Results: A total of 91 OMG patients were observed in this study with 32 (35,2%) patients converted from ocular myastenia gravis to general myastenia gravis. Median conversion time to GMG was 34 months. Risk factor for convertion cases of OMG to MGG was receiving immunosupressive agents (Risk: 14.7, 95% CI 4.83, 44.7), thymus hyperplasia (Risk: 3.36, CI 95% 0.33, 33.6), Female (Risk: 2.41, 95% CI 0.94, 6.17), Smoking (Risk: 1.56, 95% CI 0.31, 7.81). Conclusion: Ptosis was the definitive sign for OMG in this study, with all patients had ptosis, thus it needs the colaboration from neuroophthalmologist and neurologist to diagnose and manage this case. Most of converted case was female and those who receive an immunosupressive agent therapy.